Structure-dependent antiviral activity of catechol derivatives in pyroligneous acid against the encephalomycarditis virus. Issue 63 (22nd October 2018) - Li, Ruibo; Narita, Ryo; Ouda, Ryota; Kimura, Chihiro; Nishimura, Hiroshi; Yatagai, Mitsuyoshi; Fujita, Takashi; Watanabe, Takashi
Abstract : The structure-related antiviral activities of catechol and derivatives were investigated. A new strategy for producing antiviral compounds was proposed. Abstract : The pyrolysis product, wood vinegar (WV), from Japanese larch exhibited strong antiviral activity against the encephalomycarditis virus (EMCV). Catechol, 3-methyl-, 4-methyl-, 4-ethyl-, and 3-methoxycatechol, and 2-methyl-1, 4-benzenediol were identified as the major antiviral compounds. The viral inhibition ability of these compounds was affected by the structure and position of the substituent group attached to the aromatic skeleton. The IC50 of catechol was 0.67 mg mL −1 and those of its derivatives were <0.40 mg mL −1 . Methyl and ethyl substitution in the para position relative to a hydroxyl group obviously increased the antiviral activities. The mode of antiviral action was investigated by adding catechol derivatives at different times of the viral life cycle. It was found that direct inactivations of EMCV by these compounds were the major pathway for the antiviral activity. The effect of catechol derivatives on the host immune system was studied by quantification of Il6 and Ifnb1 expression levels. Increased Il6 expression levels indicate NF-κB activation by reactive oxygen species from auto-oxidations of catechol derivatives, which is also a possible antiviral route. The present research provides indices for production of potent antiviral agents form lignocellulose biomass.